The Influence Of Business Strategy On Outsourcing Human Resource Functions; A Study Of The Manufacturing Sector In Sri Lanka - Asanka, P.C.K.M.; Arachchige, B.J.H. (Proceedings of International Conference on Multidisciplinary Approaches - 2015, 2015)
Attached
Keywords: Outsourcing; Human Resource Management; Business Strategy; Sri Lanka